Metachronous, Polyostotic Aneurysmal Bone Cysts in an Adolescent Female: A Case Report. Issue 4 (October 2019) - Naylor, William M.; Collier, Christopher D.; Redline, Raymond W.; Getty, Patrick J.
Abstract : Update: This article was updated on December 18, 2019, because a new reference was added post-publication. This new reference (Niemeier TE, Leddy LR, Chapin RW, Smith TM. Metachronous Aneurysmal Bone Cysts in a Fourteen-Year-Old Girl: A Case Report and Review of the Literature. JBJS Case Connect. 2013 Jun 12;3[2 Suppl 8]:1-7) has been inserted as reference 26, and the original references 26 and 29 through 35 have been renumbered accordingly. Additionally, Table I and several passages in the text have been updated to reflect the addition of the new reference. Specifically, in Table I, the study by Niemeier et al. has been inserted as the fifth row between the "Amer et al." and "Current case" rows. On page 3, the text that had read "To our knowledge, there are only 4 published cases of metachronous, polyostotic ABCs in 4 male patients25 -28 . The longest documented interval between clinical presentation of the first and second lesions is 15 years25, whereas the shortest interval is 15 months26 ." now reads "To our knowledge, there are only 5 published cases of metachronous, polyostotic ABCs in 4 male patients and 1 female patient25 -29 . The longest documented interval between clinical presentation of the first and second lesions is 15 years25, whereas the shortest interval is 3 months26 ." On page 7, the passage that had read "However, to our knowledge, there are only 4 published cases of metachronous, polyostotic ABCs, and all patients were males25 -28 . The current case demonstrates that females may also develop polyostotic disease. None of the 4 previously reported cases of metachronous, polyostotic ABCs demonstrated a previous history of malignancy25 -28 ." now reads "However, to our knowledge, there are only 5 published cases of metachronous, polyostotic ABCs with only 1 case describing lesions in a female patient25 -29 . This is the second case demonstrating that females may also develop polyostotic disease. None of the 5 previously reported cases of metachronous, polyostotic ABCs demonstrated a previous history of malignancy25 -29 ." Also on page 7, the sentence that had read "Metachronous ABCs are rare and have been reported to present anywhere from 15 months to 15 years after diagnosis of the initial lesion25, 26 ." now reads "Metachronous ABCs are rare and have been reported to present anywhere from 3 months to 15 years after diagnosis of the initial lesion25 -29 ." An erratum has been published: JBJS Case Connect. 2019 Dec 24;9(4):e0263ER. Case: We present a case involving an adolescent female who developed metachronous, polyostotic aneurysmal bone cysts (ABCs) of the left hemipelvis and left proximal tibia within a 16-month interval. At age 12 years, the left periacetabular ABC was initially treated with selective arterial embolization and percutaneous sclerotherapy, followed by intralesional curettage and bone grafting. At age 14 years, the left proximal tibia ABC was treated with intralesional curettage, bone grafting, and prophylactic internal fixation. She showed no evidence of recurrence of either lesion after 32 and 12 months, respectively. Conclusions: Metachronous, polyostotic ABCs may occur in females. Metachronous lesions may present years after the initial ABC; therefore, additional imaging to rule out polyostotic disease is not indicated in the routine management of a solitary ABC. Patients with multiple ABCs should be managed by following the standard approach for treatment of each lesion.